Turmeric Oil Interferes with Quorum Sensing as an Alternative Approach to Control Aeromonas hydrophila Infection in Aquaculture - Jing Dong; Jian Tong; Shengping Li; Xinwei Ma; Qiuhong Yang; Yongtao Liu; Shun Zhou; Xizhi Shi; Xiaohui Ai (Biology)
Aquatic products play a crucial role in meeting the increasing global demands for high-quality proteins. However, the occurrence of bacterial diseases results in significant economic losses worldwide. Aeromonas hydrophila (A. hydrophila) is the pathogen of several fish diseases. Antibiotics were widely used in combating bacterial diseases in aquaculture. The increasing occurrences of antibiotic resistance necessitate the restricted use of antibiotics. Consequently, developing drugs that avoid antibiotic resistance is important for the future of aquaculture. Quorum sensing (QS) is critical for bacterial pathogens in regulating bacterial virulence and is a promising target for developing anti-infective agents. Here, we found that turmeric oil with a MIC of 256 μg/mL could dose-dependently reduce the virulence phenotypes regulated by QS, ranging from 8 to 64 μg/mL, suggesting that sub-inhibitory concentrations of turmeric oil could inhibit bacterial virulence. Further qPCR findings demonstrated that turmeric oil could significantly inhibit the transcription of aerA, ahyI, and ahyR by a 54-fold, 36-fold, and 56-fold change reduction, respectively. Cell live/dead staining and animal study results showed that turmeric oil could inhibit the pathogenicity of A. hydrophila. Fish treated with turmeric oil showed a reduced mortality rate of 60%, whereas all fish in the positive control group died. Moreover, treatment with turmeric oil could alleviate the renal injury. Collectively, the results suggested that targeting bacterial virulence might be a useful approach to combating bacterial infections, and turmeric oil could serve as a potential agent for combating A. hydrophila infections.